Library Research the Effect of Problem Based Learnig (PBL) Learning Model on Students Critical Thinking Skills - Elisa oktavia; Sahat Saragih (JMEA : Journal of Mathematics Education and Application, 2022)
This study aims to find out the results of a Library research using the Problem Based Learning (PBL) learning model on students' critical thinking skills. This type of research is qualitative research using the Library Research research method or library study conducted at Digital Library UNIMED for two months, starting from February to April 2022. The data analysis technique in this study used Miles and Huberman analysis technique. The data used in this study is secondary data from several literatures that are used as references in this study, the researcher conducteddata reduction and selects 4 journals and 2 theses as the main subject in conducting research.Based on the results of research and analysis obtained, it can be concluded that the Problem Based Learning (PBL) learning model has a large effect on students' critical thinking skills with the acquisition of an average effect size value of 0,95. This Shows that the effect obtained is in the large category and a series of stages in the PBL learning model are able to fulfilling indicator of students' critical thinking skills. The answer process of student also in solving problems whose learning using the PBL model has increased.